Hubungan Karakteristik Istri Nelayan dengan Pendapatan Keluarga Nelayan Kenjeran Surabaya - Setya Prihatiningtyas (Majalah Ilmiah DIAN ILMU, 2022)
The finishing community is usually identically considered as a layer of society with a low level of welfare. This can be seen from the condition of Indonesian fisherman who are still lacking in meeting the needs of their family life. The work and income of fisherman are highly dependent on the weather and seasons, so that the impact on income is uncertain. In the condition that the husband’s income as a fisherman is relatively low and uncertain, the one who can help maintain the family’s livelihood is the fisherman’s wife. This study aims to determine the relationship between the characteristics of fisherman’s wives with the family income of fisherman in Kenjeran Surabaya. This research was conducted using quantitative methods with a research sample of 20 respondents. Testing the data used in this study is the validity test, reliability test, simple linear regression analysis, F test, and the coefficient of determination using SPSS 25.0 for windows. The result of this study indicate that the characteristics of fisherman’s wives do not have a significant relationship with fisherman’s family income with the value of Fcount (1,317) < Ftable (4,38), and the value of sig. 0,289 > 0,05 then Ho is accepted and Ha is rejected. The results of the coefficient of determination (R2) obtained an effect of 15,8%, while 84,2% of fisherman’s family incomes were influenced by other variables not examined in this study.